Chronic Myeloid Leukemia Patient’s Voice About the Experience of Treatment-Free Remission Failure: Results From the Italian Sub-Study of ENESTPath Exploring the Emotional Experience of Patients During Different Phases of a Clinical Trial - Borghi, Lidia; Galimberti, Sara; Baratè, Claudia; Bonifacio, Massimiliano; Capochiani, Enrico; Cuneo, Antonio; Falzetti, Franca; Iurlo, Alessandra; Lunghi, Francesca; Minotto, Claudia; Orlandi, Ester Maria; Rege-Cambrin, Giovanna; et al. (Frontiers in Psychology, 2019)
Background. The main objective of this study is to gain further insights on how chronic myeloid leukemia (CML) patients involved in an interventional clinical trial with the purpose of reaching treatment free remission (TFR) phase, perceived and experienced TFR failure. TFR failure was defined for the individual patient as either not being eligible for drug discontinuation or as having relapse in the TFR phase with reintroduction of nilotinib treatment. Methods. Using a qualitative approach, out of 25 patients with CML who experienced TFR failure 14 were interviewed. Patients’ views and experiences were explored using in-depth interviews, analyzed using the Interpretative Phenomenological Analysis (IPA). Results. The analysis of the interviews revealed that the experience of the diagnosis seems to have been lived as a traumatic break that has created a dichotomy, like an ambivalence in the ways in which CML patients perceived and experienced the whole disease journey, with contradictory feelings of both positive and negative emotions (e.g. a diagnosis of cancer, that is something distressing and of being afraid of, but also with a treatment and a life expectancies of which being grateful). This ambivalence of feelings was found to give meaning to the way in which patients cognitively and emotionally experienced the different steps of their disease history. Thus, four main issues, corresponding to different steps of the patients’ journey, were identified: 1) the moment of the diagnosis; 2) the experience of the illness journey: disease and treatment; 3) the moment of “TFR failure”; 4) the impact of disease, treatment and relapse on the patient’s life. Conclusions. This qualitative analysis helps in understanding patients’ perspective, both in terms of getting access to the inner subjective experience of having CML and its strict relationship with the involvement in a trial or its cessation. . Clinicians should consider that the way in which CML patients feel engaged in a clinical trial, create expectancies about TFR or experience the TFR failure is linked to the process of coping with the diagnosis, which is characterized by ambivalence.